I Survived Hurricane Katrina, 2005 - Tarshis, Lauren; Dawson, Scott (New York Scholastic Inc., 2011)
Barry's family tries to evacuate before Hurricane Katrina hits their home in New Orleans. But when Barry's little sister gets terribly sick, they're forced to stay home and wait out the storm. At first, Katrina doesn't seem to be as bad as predicted. But overnight the levees break, and Barry's world is literally torn apart. He's swept away by the floodwaters, away from his family. Can he survive the storm of the century -- alone?
Ages 7-10.
RL4.
Accelerated Reader AR
Reading Counts RC
Accelerated Reader AR
Accelerated Reader
Keywords: 2005; Hurricane Katrina, 2005 -- Juvenile fiction; Floods; Survival; African American families; New Orleans (La.) -- Juvenile fiction; Louisiana -- New Orleans; Children's stories; Action and adventure fiction; Juvenile works